2015
DOI: 10.1002/oby.21212
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic supplementation and trimethylamine‐N‐oxide production following a high‐fat diet

Abstract: Objective: The objective of this study was to test the hypothesis that the multi-strain probiotic VSL#3 would attenuate the increase in fasting plasma concentrations of trimethylamine-N-oxide (TMAO) following a high-fat diet. Methods: Nineteen healthy, non-obese males (18-30 years) participated in the present study. Following a 2-week eucaloric control diet, subjects were randomized to either VSL#3 (900 billion live bacteria) or placebo (cornstarch) during the consumption of a hypercaloric (11,000 kcal day 21 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
84
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(92 citation statements)
references
References 36 publications
4
84
2
2
Order By: Relevance
“…In the present study, we found that mice fed a WD for 8 weeks developed obesity and dyslipidemia but did not significantly increase plasma glucose levels, confirming the results of a previous study (Carbone et al, 2015). Moreover, an 8 week WD feeding significantly increased plasma TMAO levels in mice, which is consistent with the finding of recent studies in human (Boutagy et al, 2015a,b), suggesting that consumption of WD may alter gut microbiota composition and function, and contribute to elevated circulating TMAO levels.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the present study, we found that mice fed a WD for 8 weeks developed obesity and dyslipidemia but did not significantly increase plasma glucose levels, confirming the results of a previous study (Carbone et al, 2015). Moreover, an 8 week WD feeding significantly increased plasma TMAO levels in mice, which is consistent with the finding of recent studies in human (Boutagy et al, 2015a,b), suggesting that consumption of WD may alter gut microbiota composition and function, and contribute to elevated circulating TMAO levels.…”
Section: Discussionsupporting
confidence: 91%
“…Animal and human studies have demonstrated a meta-organismal pathway in which the gut microbiota plays an obligatory role in the metabolism of trimethylamine (TMA) containing nutrients, such as L-carnitine, choline, and betaine (Wang et al, 2011; Wang Z. et al, 2014; Boutagy et al, 2015a). The metabolism of these constituents produces TMA, which is readily absorbed and travels via the portal circulation to the liver, where it is oxidized by hepatic flavin monooxygenase 3 (FMO3) to trimethylamine-N-oxide (TMAO; Wang et al, 2011; Wang Z. et al, 2014; Boutagy et al, 2015a). Elevated TMAO levels has recently been shown to be independently associated with increased risk of adverse cardiovascular outcomes, including heart attack, stroke, and death risk (Tang and Hazen, 2014, 2017; Tang et al, 2015b; Kitai et al, 2016; Senthong et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When we investigated whether the change of macronutrient intake and the intake of saturated fat, which is mainly derived from animal sources, correlates with the change of TMAO levels, no such relationship was found. Previous studies investigating the impact of diet modification on fasting TMAO levels revealed that a 2-week high-fat diet did not change fasting TMAO levels34, while a small increase of TMAO levels was found during a 4-week high-fat diet intervention35. Together with our data these findings indicate that fasting TMAO levels are not strongly regulated by a moderate modification of the diet that is currently being recommended for the prevention of cardiometabolic diseases36.…”
Section: Discussionsupporting
confidence: 65%
“…On the other hand, the study did not find a significant increase in fasting plasma TMAO concentrations following the short-term (5-day) high-fat diet intervention in the non-obese men 20. Another study of normal-weight individuals showed that a 4 week high-fat diet significantly increased plasma TMAO concentrations, whereas plasma L-carnitine or choline concentrations did not increase in the high-fat diet group 21. In the present study, differences in TMAO changes between low-/high-fat diet groups were not statistically significant, probably due to different characteristics of participants and study design (such as obesity status, weight changes, and duration of the diet intervention) between our study and the previous studies.…”
Section: Discussionmentioning
confidence: 63%